EFEK PENAMBAHAN ASAM SITRAT DAN LAMA PEMANASAN TERHADAP MUTU MINYAK KACANG TANAH SELAMA PENYIMPANAN - Susiloningsih, Enny Karti Basuki (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2009)
The research aims to analyze the effect of citric acid addition on the quality of peanut oil during storage. Before extracting the oil by steaming and dry heating to know the content and the peroxide value of oil 0 ppm or 200 ppm of citric acid is added to the oil produced from all treatments. The oil samples were stored for 12 weeks at 30Â°C. It is found that steaming at 90oC for 30 minutes, the oil content is 24,84% peroxide value 1.10 meq/kg oil, free fatty acid 0.017% and iodine value 89.955. Meanwhile, dry heating at 45oC without citric acid, the peroxide value 73.75 meq/kg oil, free fatty acid 0.017% and iodine value 89.995 and with citric acid 200 ppm, peroxide value 69.75 meq/kg oil, free fatty acid 0.664% and iodine value 83.685 and not rancid.